Efficiency of Power Application of Pulp and Paper Production Waste in E-75-3.9-440 DFT and KM-75-40M Fluidized Bed Boilers - Terekhin, A. P.; Maryandyshev, P. A.; Briard, A. (Power technology and engineering, 2025)
The study investigated the efficiency of two fluidized bed boiler units E-75-3.9-440 DFT and KM-75-40M installed at thermal power plant 3 of Arkhangelsk Pulp and Paper Mill. Energy studies were conducted at the steady-state thermal mode of the boiler units. The load, steam pressure, superheat temperature, excess air coefficient, feedwater temperature and its supply to the boiler were maintained approximately constant. Two tests were conducted on the E-75-3.9-440 DFT and KM-75-40M boiler units, namely during combustion of a fuel mixture of sewage sludge and bark and wood waste of coniferous wood and during combustion of a fuel mixture of sewage sludge and bark and wood waste of deciduous wood. The results of the studies revealed that the E-75-3.9-440 DFT boiler unit, designed for combustion of a mixture of bark, wood and sewage sludge waste, ensures their efficient combustion even with a decrease in the calorific value of bark and wood waste and sewage sludge due to high moisture content. The examination of the KM-75-40M boiler unit showed that burning deciduous bark and sludge requires an increase in the proportion of recirculation gases in the primary air to ensure the operating temperature of the fluidized bed.